"Caritas theory" as theological discourse within education in social work?. Issue 3 (2nd July 2020) - Opatrný, Michal
ABSTRACT: This study focuses on incorporating the field of Caritas Theory (from German "Caritaswissenschaft"), which concentrates on the theological reflection of Christian charity, into study programs in social work. First, the article reflects on the study plans of relevant programs at pertinent universities in the European 10 Union. It distinguishes these as to whether they directly contain the study of Caritas Theory or of particular theological themes. It describes the origin of the field, which differs from Catholic Social Thought, and the current discourses within the field taking place in English as well as several other European languages (German, Spanish, Czech, Polish, Hungarian). Finally, it systematizes, reflects on, and evaluates the relationship of the field to education in social work. The basic criterion is the actual contribution of Caritas Theory for studying social work. The study identifies overall four concepts of the relationship of this field to social work – the conception of "Christian social work, " the complementary model, the conception of structural similarity, and the transdisciplinary approach. According to the study, only two of these, however, fulfill the criterion of an actual contribution to studying social work.